Respuesta del rendimiento productivo de dos variedades de melón (cucumis melo, L.) a la aplicación de tres niveles de biol - Meneses Toro, Freddy Edmundo (2018)
VII. SUMMARY Farmers in the Itazán sector lack knowledge in the elaboration of organic fertilizers, as well as the lack of knowledge of new crop alternatives that mitigate the presence of pests and thus achieve sustainable and sustainable production. So the present investigation focused on evaluating the agronomic performance of two varieties of melon in order to find what is the best agronomic behavior in the treatments and thus decides what variety and what doses are appropriate for the area. We investigated eight treatments with the combination of two varieties of melon, three doses of biol and two control one for each variety, using an experimental design of Complete Blocks at random with a factorial arrangement, with 8 treatments and 3 repetitions, giving a total of 24 experimental units. The efficiency of the biol in the varieties was evaluated as to percentage of yield, length of the main axis, number of the main axis, number of fruits, fruit weight, yield and economic analysis, the data that was obtained were statistically studied in an analysis of variance with a comparison of treatments according to Duncan at 5%. The results obtained reveal that the Yellow Canary variety reacts positively to the application of the biol, improving fruit weight, yield and economic analysis. There was a difference in the cultivation of melon with the Yellow Canary variety, since they responded positively to the application of the biol in terms of length of the main axis, at 40, 50 and 80 days, the treatment (T6) reaches the highest averages, in fruit weight the T7 treatment reaching the highest weight in kilos per plant and its highest yield in kilos per hectare. Therefore, the use of Canarian Yellow Melon hybrids is recommended for sowing due to its climatic adaptability and agronomic performance.